Lung Cancer in a Sample of Iraqi Patients - Al-Rahim, Yousif A. (AL-Kindy College Medical Journal, 2007)
Background: Lung cancer is responsible for the most cancer deaths in both men and women throughout the world. Deaths from lung cancer (160,440 in 2004, according to the National Cancer Institute) exceed the number of deaths from four other major cancers combined (breast, colon, pancreatic and prostate). Objective: To assess the behavior and the approaches of lung cancer in a sample of Iraqi patients. Methods: This descriptive retrospective study was performed using the records of 390 patients proved to have lung cancer that had attending the Thoracic Surgery Department of Surgical Specialties Hospital-Medical City for the period from January, 1st , 2001 to December, 31st ,2002. Results: The results of this study revealed that 71.8% of the patients were male, with a mean age of 63 years. The majority of the patients (90.2%) were smokers, the number of cases increases with the increase in the duration of smoking or the amount of daily cigarette smoking. Radiotherapy is the primary management of 75.9% and the surgical choice was in 24.1% of the patients, but the tumors were removed only in 42.5% of operable patients. Conclusions: Lung cancer is an important and serious public health problem with an increasing in incidence and prevalence in Iraq; cough is the most common clinical finding, found in 98.5% of patients, followed by haemoptysis (64.1%); cigarette smoking is responsible for the at least 90% of its etiology. Sequamous cell carcinoma is the most common type of primary lung cancer in Iraq (42.6%) with prominence in male gender; adenocarcinoma is the second common type with equal distribution in male and female